Tariff Modifications in the Natural Gas Chain in Argentina (2018)
The objective of the work is to evaluate the impact of the tariff in the natural gas chain in Argentina c over the last years. The paper focuses on the effect of these changes between the different agents in the gaschain. Different tariff schedules that governed the sector over the last two decades are analyzed, particularly during the last years when the increase in the price of wellhead gas and the completion of the TariffReview Integral (RTI) in the transportation and distribution of natural gas segments determined a significant change in the distribution of resources within the gas chain. In this work it is shown that the processof recomposing the price of natural gas in the mouth of the well had the primary objective of reducing the subsidies received by the producing companies through the Gas Plan I and II. It is concluded that the increase in gas tariffs allowed a reduction in energy subsidies and although it generated a sensible transfer of resources from consumers, the main beneficiary was the central government and, in second order, thenatural gas distribution and transport companies., while the producing companies of hydrocarbons were barely benefited by these measures.